2017
DOI: 10.18203/2319-2003.ijbcp20173750
|View full text |Cite
|
Sign up to set email alerts
|

Study of drug prescription pattern among COPD patients admitted to medicine in-patient department of tertiary care hospital

Abstract: Background: Drug utilization studies can provide insights into a pattern, quality, determinants and outcomes of drug use. COPD is one of the leading causes of death among Indian population and there is a lack of drug utilization studies in this field.Methods: A prospective, observational study was conducted among the patients admitted in inpatient department of medicine ward of Tertiary care hospital. Data has collected from COPD patients admission records. Parameters like demographic profile, common associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 6 publications
5
7
0
Order By: Relevance
“…Results showed that COPD occurs more in men than in women, which get confirmed by demographic assessment and could be largely due to cigarette smoking and other causes like low socioeconomic status and occupational exposure to vapor, dust, gas and fumes. This finding was found in accordance with results of the previous studies conducted by Unni A et al 11 and Sawant PM et al 12 .…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Results showed that COPD occurs more in men than in women, which get confirmed by demographic assessment and could be largely due to cigarette smoking and other causes like low socioeconomic status and occupational exposure to vapor, dust, gas and fumes. This finding was found in accordance with results of the previous studies conducted by Unni A et al 11 and Sawant PM et al 12 .…”
Section: Discussionsupporting
confidence: 94%
“…The stress, age, lifestyle modifications may also contribute to hypertension. The result representing hypertension as the mostly found co-morbid condition had similarity with previous studies conducted by Unni A et al 11 , Sawant MP et al 12 and Mahmoodan M et al 17 .…”
Section: Discussionsupporting
confidence: 90%
“…Out of 200 patients, following results were found and findings are presented through pie-chart, tabulations and bar graphs. [5] . Table 2 shows that higher number of female patient (58%) were found than male patient (42%).…”
Section: Resultsmentioning
confidence: 99%
“…COPD prevalence is 5.0% among Indian males and approximately 3.2% among Indian females over 35 years of age. 4 It is projected to be the 3 rd leading cause of death by 2030. According to a recent systematic review which includes estimates from the INSEARCH and other major studies in India, the prevalence of CB seems to range between 6.5% and 7.7% in rural and up to 9.9% in urban India.…”
Section: Introductionmentioning
confidence: 99%
“…Irrational use of drugs is a major concern in modern clinical practice, more than half of all medicines are prescribed, dispensed or sold inappropriately. 4 Although COPD is a progressive, incurable disease, pharmacological treatment can help control symptoms, reduce exacerbations and improve exercise tolerance and health status. The mainstay of pharmacological therapy for COPD is bronchodilation with a long-acting muscarinic antagonist (LAMA), a long-acting β2-agonist (LABA), or a combination of the two, depending on the severity of breathlessness and the patient's risk of exacerbations.…”
Section: Introductionmentioning
confidence: 99%